FINANCIAL DISTRESS IN INDONESIAN PROPERTY AND REAL ESTATE COMPANIES: THE INFLUENCE OF LEVERAGE, PROFITABILITY, LIQUIDITY, AND CORPORATE GOVERNANCE - Reni Kartini; Dani Sopian (ZILLZELL MEDIA PRIMA, 2026)
This study aims to analyze the influence of leverage, profitability, liquidity, and corporate governance on financial distress in property and real estate companies listed on the Indonesia Stock Exchange for the 2020–2024 period. The research uses a quantitative approach with secondary data in the form of the company's annual financial statements. The research sample consisted of 54 companies with a total of 270 observations selected using purposive sampling techniques. The data analysis technique uses multiple linear regression. The results of the study show that leverage has a significant negative effect on financial distress, while profitability and liquidity have a significant positive effect. Corporate governance has no significant effect on financial distress. Simultaneously, all independent variables have a significant effect on financial distress. The Adjusted R Square value of 0.435 indicates that 43.5% of the variation in financial distress can be explained by the research model. This study shows that financial distress conditions are influenced by a combination of financial performance factors and corporate governance.